Pengaruh High Performance Work System terhadap Employee Creativity, Employee Performance dan Entrepreneurial Orientation - Ni Kadek Ayu Kusherawati; Tantri Yanuar Rahmat Syah (LPPM Universitas BSI, 2022)
This research was conducted to explore the effect of High Performance Work System on Entrepreneurship Orientation, Employee Creativity as a mediating variable by employee performance and Entrepreneurship Orientation as mediating by employee performance. This research is expected in information enhancement at the organizational theory/scientific level as well as improving the performance of work systems in the energy industry. This study resulted several findings, the High Performance Work System had a significant positive effect on Employee Creativity. The High Performance Work System was no significant negative effect on Employee Performance. Employee Creativity was no significant negative effect on Employee Performance. Thus, there was an insignificant negative effect on the mediating role of Employee Creativity on the relationship between High Performance Work System and Employee Performance. High Performance Work System was a significant positive effect on Entrepreneurial Orientation. Entrepreneurial Orientation was a positive effect on Employee Performance. Thus, there was a positive influence on the mediating role of Entrepreneurial Orientation on the relationship between High Performance Work System and Employee Performance. Keyword: High Performance Work System, Employee Performance, Employee Creativity, Entrepreneurial Orientation